Legends Of People, Myths Of State : Violence, Intolerance, and Political Culture in Sri Lanka and Australia. - Kapferer, Bruce (Smithsonian series in ethnographic inquiry Legends of people, myths of state, 2011)
The civil war in Sri Lanka and the part that nationalism seemed to play in it inspired the writing of this book some twenty-three years ago. The argument was developed through a comparative analysis of nationalism in Sri Lanka with the author's native Australia. At the time this constituted an innovative approach to comparison in anthropology, as well as to nationalism and its possibilities. It was not based on differences but on the way in which perspectives from within the two nationalisms, when seen side-by-side, could present an understanding of their implication in producing the violence.